Pacific Warming Pattern Diversity Modulated by Indo‐Pacific Sea Surface Temperature Gradient. Issue 23 (30th November 2021) - Zhang, Leying; Zhao, Jiuwei; Kug, Jong‐Seong; Geng, Xin; Xu, Haiming; Luo, Jingjia; Park, Jae‐Heung; Zhan, Ruifen
Abstract: The multi‐model ensemble mean sea surface temperature (SST) of CMIP5 models shows an El Niño‐like Pacific warming (PW) trend, contradictory with the observational result which manifests a La Niña‐like PW pattern. Here, we demonstrate that these two SST PWs coexist in the CMIP5 models and they are largely determined by the model's tropical Indo‐Pacific SST gradient. When the Pacific warms faster than the Indian Ocean (IO), the model tends to project an El Niño‐like PW pattern. In contrast, a La Niña‐like warming trend prevails if a more rapid IO warming is simulated. We suggest that the PW pattern in an individual model is nonstationary and may transform from a La Niña‐like to an El Niño‐like when its interbasin SST gradient changes with more robust warming in the Pacific, and vice versa. Our conclusions shed great light on the future SST PW pattern change projected by the coupled models. Plain Language Summary: Previous studies demonstrate that an El Niño‐like SST warming pattern prevails in a majority of CMIP5 models. But a La Niña‐like warming pattern is detected based on historical SST records. This inconsistency between the observations and model simulation triggers an intense debate in the climate community. In this study, we find that both El Niño‐like and La Niña‐like SST warming patterns can be identified in the CMIP5 model simulations. The warming pattern is largely determined by the SST gradient between the Indian and Pacific oceans. Distinct from previous studies, an El Niño‐like pattern in an individual model can shift to a La Niña‐like pattern when the Indian warming is stronger than the Pacific warming trend, and vice versa. Key Points: El Niño‐like and La Niña‐like Pacific sea surface temperature warming patterns coexist and are interchangeable in climate model projections The tropical Pacific warming pattern is primarily determined by a zonal gradient in the Indo‐Pacific sea surface warming This Pacific warming pattern diversity sheds light on future sea surface temperature change under greenhouse gases concentrations